PENGARUH GAYA KEPEMIMPINAN DEMOKRATIS TERHADAP KINERJA KARYAWAN - Turmono (Jurnal Teknologi dan Bisnis, 2020)
This study aims to determine the influence of democratic leadership on the employee performance of the various business projects run by Ciputra University’s students from the class of 2014. This research is a quantitative research which uses random sampling as sampling technique. The research population is taken from the International Business Management (IBM) department; more specifically, IBM students from the class of 2014 who are not the CEOs of their business projects. The population criteria also exclude family businesses and any business managed by one person. The research population amounts to 167 students, from which 118 are selected as research samples. Likert-scale questionnaire is used to retrieve research data, while simple regression analysis is used to analyze the data. The F test indicates a significance value of <0.05. Likewise, the t test result is shown as <0.05. Therefore, it can be concluded that the democratic leadership style, which acts as the independent variable in this research, significantly affects the employee performance as the dependent variable.